2023
DOI: 10.1177/17474930231182901
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous sinus thrombosis due to vaccine-induced immune thrombotic thrombocytopenia in middle-income countries

Abstract: Background: Adenovirus-based COVID-19 vaccines are extensively used in low- and middle-income countries (LMICs). Remarkably, cases of cerebral venous sinus thrombosis due to vaccine-induced immune thrombotic thrombocytopenia (CVST-VITT) have rarely been reported from LMICs. Aims: We studied the frequency, manifestations, treatment, and outcomes of CVST-VITT in LMICs. Methods: We report data from an international registry on CVST after COVID-19 vaccination. VITT was classified according to the Pavord criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Comparative research between middle-income (MIC) and high-income countries (HIC) reported CVST cases post-vaccination, noting a lower in-hospital mortality rate in MICs. 45 This study also pointed out the infrequent testing for anti-PF4 antibodies in MICs, a key diagnostic marker for VITT, suggesting variations in diagnostic and management practices across different settings.…”
Section: Cerebral Venous Sinus Thrombosismentioning
confidence: 67%
See 1 more Smart Citation
“…Comparative research between middle-income (MIC) and high-income countries (HIC) reported CVST cases post-vaccination, noting a lower in-hospital mortality rate in MICs. 45 This study also pointed out the infrequent testing for anti-PF4 antibodies in MICs, a key diagnostic marker for VITT, suggesting variations in diagnostic and management practices across different settings.…”
Section: Cerebral Venous Sinus Thrombosismentioning
confidence: 67%
“… Kerr et al 43 Self-controlled case series 11.6 million in England, Scotland, Wales >16years Oxford-AstraZeneca, Pfizer-BioNTech 1st Dose Increased risk of CVST after vaccination with ChAdOx1 nCoV-19, but not after BNT162b2. McKeigue et al 44 Case-crossover study 6,894,008 vaccination doses, 50 CVST cases All age groups AstraZeneca, Pfizer-BioNTech, Moderna 1st and 2nd doses Causal association between CVT and AstraZeneca vaccine Van de Munckhof et al 45 International observational study More than 12 billion vaccination doses, 228 CVST cases All age groups All vaccines Not specified Lower in-hospital mortality rate in middle-income countries compared to high-income countries for CVST-VITT cases. …”
Section: Cerebral Venous Sinus Thrombosismentioning
confidence: 99%
“…66 More surprisingly, no cases were reported from low-income countries. 66 This difference may be attributed to misdiagnosis or underdiagnoses of CVT along with the lack of laboratory confirmation in these countries but despite this, we would have expected more cases. It is possible that the CVT-vaccine-induced immune thrombotic thrombocytopenia (VITT) risk differs among populations.…”
Section: Covid-vaccine-related Cvtmentioning
confidence: 97%
“…65 Interestingly, a large international registry showed a lower incidence of CVT in middle-income countries along with low mortality despite the predominant use of the adenovirus vaccines as compared to high-income countries. 66 More surprisingly, no cases were reported from low-income countries. 66 This difference may be attributed to misdiagnosis or underdiagnoses of CVT along with the lack of laboratory confirmation in these countries but despite this, we would have expected more cases.…”
Section: Covid-vaccine-related Cvtmentioning
confidence: 97%
“…131 While CSVT-VITT results in high in-hospital mortality rates in the acute phase, patients who survive initial hospitalization have a favorable prognosis, with almost 90% of patients achieving functional independence at 150 day follow-up according to one study. 132 Papilledema has rarely been reported as a complication of the COVID-19 vaccine. In one case, a 45-year-old woman developed bilateral papilledema secondary to VITT 8 days after administration of the AstraZeneca vaccine.…”
Section: Afferent Complications Associated Temporally With Sars-cov-2...mentioning
confidence: 99%